Analisis Manajemen Risiko Operasional pada Usaha Dekorasi Panggung dan Tenda Menggunakan ISO 31000:2018 - Dena Destiani; Syahira Rachmadina; Fidelairna Daniswara; Najla Putri Pramesdianti; Alfiana (Indo Publishing, 2025)
Stage and tent decoration services are part of the MSME sector that play an important role in supporting various community events such as weddings, school activities, and government programs. However, its operations face several risks, including equipment damage, weather changes, late payments, and market competition. Therefore, effective risk management is needed to maintain business continuity. This study aims to analyze operational riks and management strategies in Tiga Dara Decoration located in Sumedang Regency. The research uses a descriptive qualitative method with data collected through in-depth interviews and observations. The analysis refers to the ISO 31000:2018 framework, which includes the stage of risk identification, analysis, evaluation, and treatment. The results show that the high-level risks include delayed payments, increased operational costs, new competitors, and extreme weather. Mitigation strategies include improving service quality, applying down payment systems, cost efficiency, and providing backup equipment.